2017
DOI: 10.3389/fmicb.2017.01179
|View full text |Cite
|
Sign up to set email alerts
|

Detection of Ophiocordyceps sinensis and Its Common Adulterates Using Species-Specific Primers

Abstract: Ophiocordyceps sinensis is a fungus that infects Hepialidae caterpillars, mummifying the larvae and producing characteristic fruiting bodies (stromata) that are processed into one of the most valued traditional Chinese medicines (TCM). The product commands a very high price due to a high demand but a very limited supply. Adulteration with other fungi is a common problem and there is a need to test preparation for the presence of the correct fungus. In the current study, a PCR-based approach for the identificat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 28 publications
0
15
0
Order By: Relevance
“…The identification of authentic species has become a crucial issue for the quality control of food and medicinal sources, because most of these materials are collected from wild habitats or are cultivated on farms [ 34 ]. Since the accurate identification of fungal species is very difficult, depending on the conventional method used, more reliable and objective methods are required in order to discriminate between strains at the species level [ 3 ]. In this study, we developed a simple PCR assay method, and confirmed that the comparative analysis of nrDNA-ITS sequences is one of the most reliable tools for overcoming these difficulties.…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…The identification of authentic species has become a crucial issue for the quality control of food and medicinal sources, because most of these materials are collected from wild habitats or are cultivated on farms [ 34 ]. Since the accurate identification of fungal species is very difficult, depending on the conventional method used, more reliable and objective methods are required in order to discriminate between strains at the species level [ 3 ]. In this study, we developed a simple PCR assay method, and confirmed that the comparative analysis of nrDNA-ITS sequences is one of the most reliable tools for overcoming these difficulties.…”
Section: Discussionmentioning
confidence: 99%
“…Gmel.) Fr., are repeatedly used as adulterants of authentic Cordyceps [ 1 , 3 ]. Furthermore, only two species, C. militaris and Isaria tenuipes Peck (syn.…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations